Abnormal Activity of Masticatory Muscles in Patients with Diagnosis of Cerebral Palsy. A Systematic Review and Meta-Analysis of Observational Studies - Beltramin, Rafael Zaratin; Martimbianco, Ana Luiza Cabrera; Gonçalves, Marcela Leticia Leal; Rocha, Monise Mendes; Silva, Soraia Micaela; Horliana, Anna Carolina Ratto Tempestini; Santos, Elaine Marcílio; Turcio, Karina Helga [UNESP]; Mesquita-Ferrari, Raquel Agnelli; Fernandes, Kristianne Porta Santos; Motta, Lara Jansiski; Bussadori, Sandra Kalil (Taylor & Francis, 2023)
Aims: to map and synthesize the results from studies that assessed whether individuals diagnosed with cerebral palsy (CP) have abnormal masseter and temporal muscles activation during the masticatory cycle. Methods: Six databases were searched for comparative observational studies assessing masticatory muscles activation in individuals with CP through electromyography analysis. Methodological quality was evaluated using the Joanna Briggs Critical Appraisal Checklist. Outcome data were combined in meta-analysis using the Review Manager software. Results: We included five cross-sectional studies with an overall low risk of bias. Meta-analyses showed no difference between CP and healthy individuals regarding maximum voluntary isometric contraction: right masseter (Standard mean difference [SMD] − 0.95; 95% CI −2.03 to 0.13); left masseter (SMD −0.92; 95% CI −1.93 to 0.09); right temporal (SMD −0.72; 95% CI −1.63 to 0.18); and left temporal (SMD −0.68; 95% CI −1.76 to 0.40). Electrical activity amplitude in the inactive period was superior in the CP group, and maximum bite pressure presented higher values in the control group (Mean difference [MD] − 17.38; CI 95% −26.62 to −10.15). Conclusions: Based on observational studies with a lower level of evidence, individuals with CP seem to present difficulties activating masticatory muscles. Future prospective cohort studies with rigorous methodology are still necessary to support these findings. PROSPERO register CRD42020208444.
Keywords: Cerebral palsy; electromyography; evidence-based practice; masticatory muscles; systematic review